Occurrence of Dental Disorders in Dogs - Sauer, Leonardo; Gualberto Oliveira, Nina Gabriela Silva; Andrade, Lorena Priscila Oliveira; da Silva, Elisângela Barbosa; de Lavor, Mário Sérgio Lima; Wenceslau, Amauri Arias; Alberto Carlos, Renata Santiago (Acta Scientiae Veterinariae, 2018)
Background: The anatomy of the canine oral cavity and its variations should be understood to facilitate clinical and surgical approaches. Several conditions can be identified during inspection of the oral cavity, including persistent deciduous teeth, enamel hypoplasia, gingival retraction, tooth abrasion and mobility, absence of dental elements, and periodontal disease. The aim of the present study was to determine the occurrence of dental disorders in dogs older than one year, from the microrregion Ilhéus - Itabuna, Bahia, Brazil. Materials, Methods & Results: A total of 74 dogs were evaluated immediately prior to surgical procedures for periodontal disease treatment. After visual inspection and examination with a millimeter probe, the dogs were classified into three groups according to the degree of periodontal disease. All other findings were recorded on an odontogram. Of the 74 dogs, 23 were classified as mild periodontal disease (mean age, 3.6 years), 26 as moderate periodontal disease (mean age, 5.7 years), and 25 as severe periodontal disease (mean age, 9.7 years). There was significant correlation (0.7 p ≤ 0.01) between age and severity of periodontal disease. Fifteen of the 74 dogs did not present any other dental disorder than periodontal disease. Of the remaining 59, nine showed a single dental problem, and 50 had more than one dental problem. Six dogs (of the breeds Pinscher, Yorkshire Terrier, and Lhasa Apso) had deciduous teeth. Of the nine deciduous teeth, all were canine (dental elements 104, 204, and 304). Ten dogs had dental fractures and of the 11 fractured teeth, three were canine (dental elements 104 and 404). Dental wear was observed in 25 dogs (154 teeth). Of the evaluated dogs, seven showed furcation defects and 10 had teeth mobility. Dental absence was observed in 47 dogs. Discussion: In the present study, increased age had a positive correlation with the degree of periodontal disease; this is consistent with reports in the literature, which indicate severity of periodontal disease increases with advancing age. In one of the three cases of enamel hypoplasia, the dog owner reported that the dog presented clinical signs compatible with distemper before the teeth changed, corroborating studies that showed that this virus can act on the enamel cells causing hypoplasia lesions. All the deciduous teeth found were dental elements 104, 204, and 304, consistent with literature reports that these teeth are among the most frequently affected by this condition. In the present paper, of all the teeth examined, the canine teeth presented the majority of fractures. Canine teeth are used for grasping and tearing food, and defense, and are more vulnerable to fractures. Dental wear was observed in many dogs in the present study, presenting as loss of dental surface caused by friction, abrasion, or erosion from a variety of causes. Dental wear may be considered as a physiological process as long as it does not compromise function. Dental mobility is an important clinical sign of periodontal disease and generates pain and discomfort to the patient; in the presence of advanced periodontitis, there is a marked loss of periodontal tissues, including alveolar bone, which is an irreversible process. As the dogs evaluated in the present study were older than one year, any absent teeth could be verified as being due to periodontal disease. In conclusion, disorders of the oral cavity have high prevalence in dogs and must receive special attention to be properly diagnosed and treated.